DETERMINAN FAKTOR INTERNAL DAN EKSTERNAL TERHADAP NILAI PERUSAHAAN FOOD AND BEVERAGE DI BURSA EFEK INDONESIA - Ameilia Damayanti; Mira Munira (InFestasi, 2019)
Companies with good financial performance will produce maximum profits so that they have a high return on investment. The purpose of this study is to prove and explain the effect of profitability (ROA), leverage (DER), and inflation partially to PBV of food and beverage companies listed on the Indonesia Stock Exchange (IDX), as well as the effect of profitability (ROA), leverage (DER), and inflation simultaneously to PBV at food and beverage companies listed on the IDX. The data used in the study are secondary data, in the form of audited financial statements of companies listed on the Indonesia Stock Exchange. The study population was 10 food and beverage companies listed on the IDX in 2012 - 2017 with the sampling technique used was purposive sampling. The analysis was carried out with quantitative descriptive analysis techniques using IBM SPSS 21. The results of data analysis showed that partially ROA had a significant effect on PBV, DER and inflation partially had no significant effect on PBV. Simultaneously ROA, DER, and inflation have a significant influence on the PBV of food and beverage companies listed on the IDX.